The Conflicts Surrounding Establishment of Places of Worship: A Structuration Analysis of GKI Yasmin Bogor - Anam, M. Syaeful; Mahmudi, Mukh. Imron Ali (Masyarakat: Jurnal Sosiologi, 2022)
This article aims to map out the conflict over the establishment of GKI Yasmin Church in Bogor, which has occurred since 2006, by looking at the dialectic relations among its sociological dimensions. The Structuration theory of Anthony Giddens is utilized to analyze relationships between structure and agency. However, previous studies have also pointed out that cultural aspects cast a wide influence on this conflict. As such, this paper also uses Paulus Wirutomo’s triadic conception of Structure, Process, and Culture, in which the latter will be explained in-depth to outline the role of cultural hegemony in reproducing the Structure of GKI Yasmin’s conflict. Our study found that structural dimensions, as the result of pragmatic calculations of state actors, resulted in the exclusion of the GKI Yasmin group. Cultural pressure, too, increasingly complicates the efforts of religious minorities to challenge this domination as it also proliferates intolerant culture. Finally, the processual dimension comprises the relations among actors with competing interests, in which masses can (re)negotiate and reproduce structural relations. The novelty of this study lies in the dialectical and holistic conflict-mapping to demonstrate how power relations work through structural, processual, and cultural dimensions. Meanwhile, previous studies have only focused on the role of the government, intolerant culture, and socio-political dimensions in the conflict of GKI Yasmin in particular, and the establishment of places of worship in general.